The impact of housing transformation to livability in North Bandung Peri-urban area (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Urbanization is an undeniable phenomenon that happens globally, including in Indonesia. Indonesian cities are growing, causing urban sprawl and transformation of rural areas into urban areas. In between the urban and rural there is peri-urban area that has unique mixed characteristics of both. Areas with such characteristics can be found easily in the outskirts of Bandung city. The growth of peri-urban areas in Bandung occurs simultaneously with the growing tourism industries. This phenomenon caused a spatial transformation especially to the existing houses, which gives impacts to the livability of the area. This article would focus upon how housing transformation in peri-urban areas can affect the livability of the area by using the North Bandung peri-urban area as a case study. The result shows that the spatial transformation that happens in peri-urban areas gives positive impacts to social, economy, and spatial aspects, but unfortunately not the environmental aspects.
Keywords: Housing transformation; Livability; Peri-urban area; Tourism impacts